Coherent lensless X-ray imaging - Chapman, Henry N.; Nugent, Keith A. (Nature photonics, 2010)
Very high resolution X-ray imaging has been the subject of considerable research over the past few decades. However, the spatial resolution of these methods is limited by the manufacturing quality of the X-ray optics. More recently, lensless X-ray imaging has emerged as a powerful approach that is able to circumvent this limitation. A number of classes of lensless X-ray imaging have been developed so far, with many based on other forms of optics. Here we report the key progress in this area, describe the potential applications for biology and materials science, and discuss the prospect for imaging single molecules using X-ray free-electron lasers.